Leachable Phosphorus Levels of Urban Street Trees: Contributions to Urban Runoff - (:unkn) unknown (My University, 1979)
Intelligent environmental management of urban areas depends upon a thorough understanding of urban ecosystem properties, such as structure, energy flow and materials cycles. This report examines the phosphorous cycle in urban runoff - a portion of the urban phosphorous cycle - which is involved in diffuse (non-point) source pollution from urban areas. The goals of my research were to determine if street tree leaves and seeds are a source of phosphorous in urban runoff and if so, how these levels varied between tree species.
Keywords: leaf phosphorus; urban trees